Numerical and experimental investigation of tsunamis generated by iceberg calving - Chen, Fan (2021)
With climate change as an increasingly important issue, the Greenland and Antarctic ice sheets have suffered rapid ice mass losses contributing to sea level rise. Iceberg calving is one of the main factors for ice mass loss and may also generate large tsunamis when icebergs calve into a water body, threatening the fishing and shipping industries and coastal communities. One of the most impressive tsunamis generated by iceberg calving with an amplitude of 45 to 50 m was observed at the Eqip Sermia glacier in Greenland in 2014. Herein, such tsunamis are called iceberg-tsunamis (IBTs).